Long-term potentiation and neurotransmitters expression and segregation are altered in the Metabolic Syndrome-associated dysautonomia - Diana Elinos; Fernanda Veladiz-Gracia; Constanza González-Sierra; Angel Rubio-Galicia; Fredy Cifuentes; Miguel A. Morales (PLoS ONE, 2025)
The autonomic nervous system (ANS) dynamically regulates the internal environment to maintain homeostasis. The ANS exhibits some forms of synaptic plasticity, including long-term potentiation (LTP) and plastic changes in neurotransmitter distribution, both of which may contribute to autonomic function. Dysautonomia refers to an abnormality in the function of the ANS, with an imbalance between sympathetic and parasympathetic activity. Dysautonomia has been reported in conditions such as stress, hypertension, and metabolic syndrome (MS). MS is a cluster of risk factors for cardiovascular disease, diabetes, and premature death. In MS, the signs of dysautonomia include elevated plasma norepinephrine levels and increased arterial blood pressure. In this study, we characterized the effect of a high-sucrose diet (HSD) on synaptic plasticity in sympathetic ganglia of the rat by measuring LTP expression in the superior cervical ganglion (SCG) and analyzing the expression of acetylcholine (ACh) and GABA, as well as their balance of colocalization/segregation in ganglionic nerve terminals. The HSD consists of adding 30% sucrose to drinking water, which is an accepted model of MS. We observed an impairment in LTP expression, along with a decrease in ACh presence and a reduction in its segregation from GABA. These findings suggest the emergence of an inhibitory effect on synaptic transmission and plasticity within the SCG. We propose that dysautonomia associated with MS might involve changes in sympathetic activity, at least at the level of ganglionic cholinergic transmission. These results may help to improve our understanding of autonomic dysfunction in the context of this metabolic disorder.